Lentinula edodes (Shiitake) modulates chemically induced mutagenesis by enhancing pitting - Alves de Lima, Patrícia L. [UNESP]; Sugui, Marina M. [UNESP]; Petrício, Angela I.M. [UNESP]; Vilela, Lízia C. [UNESP]; Pinto, Andréa V.F. [UNESP]; Martins, Priscila R. [UNESP]; Kaneno, Ramon [UNESP]; Ribeiro, Daniel A.; Salvadori, Daisy Maria Favero [UNESP]; Ribeiro, Lúcia Regina [UNESP] (SAGE Publications, 2013)
This study was undertaken to understand how Lentinula edodes modulates in vivo mutagenesis induced by alkylating agents in bone marrow and peripheral blood as described in our previous article. Male Swiss mice were pretreated for 15 consecutive days with aqueous extracts prepared from L. edodes, after which, the number of circulating blood cells, normal erythroid bone marrow cell cycling, and phagocytosis of micronucleated reticulocyte (MNRET) and activation of spleen macrophages were assessed. The results indicate that the antimutagenicity seen in bone marrow and peripheral blood is exerted by distinct compounds with different actions. The antimutagenic effect in bone marrow is exerted by compounds subject to degradation at deep-freeze storage temperature of -20 C. On the other hand, compounds responsible for antimutagenicity in peripheral blood are not subject to degradation at -20 C. The results also indicate that the antimutagenic action in peripheral blood leading to the reduction of circulating MNRET occurs in the spleen primarily through a phagocytic activity due to higher macrophage numbers and probably not due to the enhanced activation state of individual cells. © Mary Ann Liebert, Inc.
Keywords: culling; macrophages; micronucleus; pitting; hydrogen peroxide; Lentinula edodes extract; animal experiment; blood; bone marrow; bone marrow cell; controlled study; enzyme immunoassay; fluorescence microscopy; immunomodulation; in vivo study; Lentinula edodes; macrophage; male; micronucleated reticulocyte; micronucleus test; mouse; mushroom; mutagenesis; nonhuman; phagocytosis; priority journal; reticulocyte; spleen; spleen cell; storage temperature